2005
DOI: 10.1016/j.jclinepi.2005.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Best reproducibility of the ankle–arm index was calculated using Doppler and dividing highest ankle pressure by highest arm pressure

Abstract: Background and Objective: To investigate which method of ankle-arm index (AAI) measurement in terms of selected arteries and blood pressure devices yields the highest reproducibility.Study Design and Setting: In this cross-sectional study, duplicate AAI measurements were obtained at the right and left side in 320 postmenopausal women. Analyses were done as proposed by Bland and Altman and intraclass correlation coefficients were calculated.Results: The mean and standard deviation (SD) of the first and second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…147 Similarly, the intraobserver and interobserver reproducibilities are poorer for the auscultation than for the Doppler method. 197 No reproducibility data are available for the plethysmographic method.…”
Section: Are the Different Methods Of Abi Measurement Similarly Repromentioning
confidence: 99%
“…147 Similarly, the intraobserver and interobserver reproducibilities are poorer for the auscultation than for the Doppler method. 197 No reproducibility data are available for the plethysmographic method.…”
Section: Are the Different Methods Of Abi Measurement Similarly Repromentioning
confidence: 99%
“…Para a medida da pressão arterial em MMSS e MMII foi usado aparelho de tensiômetro de adulto com adequação do manguito ao biotipo do paciente e seguindo as orientações da Sociedade Brasileira de Hipertensão (32) . O ITB foi calculado de maneira habitual, razão entre a maior pressão sistólica (PS) no tornozelo e a maior PS braquial, obedecendo-se a seguinte interpretação: > 1,3 artérias incompressíveis; 0,9 a 1,3 normal; 0,75 a 0,9 doença arterial periférica bem compensada; 0,4 a 0,75 moderadamente compensada; < 0,4 grave (29,36) . No presente estudo o ponto de corte definido para o ITB foi menor que 0,9 para detecção de doença arterial periférica, com sensibilidade de 95% e especificidade de 100%, quando comparados à arteriografia, padrão-ouro de diagnóstico (13) .…”
Section: Study Of Macrovasculature By Doppler Ultrasound In Systemic unclassified
“…7,10 Information has been published about the variability of ABI measurements. [10][11][12][13][14][15][16][17][18][19][20][21][22] In general, in these studies, the variability is expressed as a percentage of the average observed ABI values ranging from 8% to 16%, whereas in absolute values the standard deviation of the difference of repeated ABI measurements was between ±0.10 and ±0. 15.…”
Section: Introductionmentioning
confidence: 99%